Multicriteria and multiagent decision making with applications to economics and social sciences - Maturo, Antonio; Hoskova-Mayerova, Sarka; Kacprzyk, Janusz; Ventre, Aldo G. S. (Studies in Fuzziness and Soft Computing, 2013)
The book provides a comprehensive and timely report on the topic of decision making and decision analysis in economics and the social sciences. The various contributions included in the book, selected using a peer review process, present important studies and research conducted in various countries around the globe. The majority of these studies are concerned with the analysis, modeling and formalization of the behavior of groups or committees that are in charge of making decisions of social and economic importance. Decisions in these contexts have to meet precise coherence standards and achieve a significant degree of sharing, consensus and acceptance, even in uncertain and fuzzy environments. This necessitates the confluence of several research fields, such as foundations of social choice and decision making, mathematics, complexity, psychology, sociology and economics. A large spectrum of problems that may be encountered during decision making and decision analysis in the areas of economics and the social sciences, together with a broad range of tools and techniques that may be used to solve those problems, are presented in detail in this book, making it an ideal reference work for all those interested in analyzing and implementing mathematical tools for application to relevant issues involving the economy and society.